Rac-GTPases Regulate Microtubule Stability and Axon Growth of Cortical GABAergic Interneurons - Tivodar, Simona (Cereb Cortex, 2015)
Cortical interneurons are characterized by extraordinary functional and morphological diversity. Although tremendous progress has been made in uncovering molecular and cellular mechanisms implicated in interneuron generation and function, several questions still remain open. Rho-GTPases have been implicated as intracellular mediators of numerous developmental processes such as cytoskeleton organization, vesicle trafficking, transcription, cell cycle progression, and apoptosis. Specifically in cortical interneurons, we have recently shown a cell-autonomous and stage-specific requirement for Rac1 activity within proliferating interneuron precursors. Conditional ablation of Rac1 in the medial ganglionic eminence leads to a 50% reduction of GABAergic interneurons in the postnatal cortex. Here we examine the additional role of Rac3 by analyzing Rac1/Rac3 double-mutant mice. We show that in the absence of both Rac proteins, the embryonic migration of medial ganglionic eminence-derived interneurons is further impaired. Postnatally, double-mutant mice display a dramatic loss of cortical interneurons. In addition, Rac1/Rac3-deficient interneurons show gross cytoskeletal defects in vitro, with the length of their leading processes significantly reduced and a clear multipolar morphology. We propose that in the absence of Rac1/Rac3, cortical interneurons fail to migrate tangentially towards the pallium due to defects in actin and microtubule cytoskeletal dynamics.